Effects of thermo-mechanical and chemical processes on the nutritional and functional quality of Sacha inchi (Plukenetia volubilis) flour - Narváez Cadena, Ruby Aracely; Roa Acosta, Diego Fernando; Bravo Gómez, Jesús Eduardo (Frontiers in Sustainable Food Systems, 2025)
The objective of this study was to subject Sacha inchi (TA) kernels to mechanical (TST), thermo- mechanical (TCT), and chemical (TMH) processes with the aim of obtaining cakes with a high protein content. These were then compared with commercial brands (TP and HC). Proximate analysis, anti-radical capacity (determined using DPPH and ABTS assays), reducing capacity (evaluated using the FRAP assay), and antinutritional compounds (tannins, phytates, and saponins) were quantified. The TCT and TP treatments exhibited relatively low contents of tannins (3.78 ± 0.01 and 2.55 ± 0.02 mg/100 g sample), phytates (3.073 ± 0.004 and 3.214 ± 0.001 mg/100 g sample), and saponins (0.496 ± 0.005 and 0.437 ± 0.002 mg/100 g sample) in comparison to the treatments (TST and HC). Accordingly, TCT, TP, and TMH were selected for the determination of rheological properties and in vitro protein digestibility, as well as the evaluation of interfacial potential at varying pH (4, 5, 7, 9) and temperatures (25 °C, 40 °C, 55 °C). The thermo-mechanical and chemical treatments result in alterations to the configuration of the proteins, which are characterized by the formation of specific secondary structures, including β-sheets, random coils, α-helices, and β-turns. These structural changes impact the interfacial potential of the proteins, influencing the particle size and the zeta potential. The results indicated that the structural changes caused by the treatments could optimize the use of Sacha inchi protein cakes in the food industry, favoring their functionality and use in the development of new products.